Răspunsuri

2014-10-18T16:14:57+03:00

d=i·c+r⇒ d-r=i·c  ⇒ i·c=6 ⇒ d=6+r  r∈{0,1,2,3,4,5}  ⇒

d∈{6,7,8,9,10,11} i∈{6,3,2}  c∈{1,2,3}

a) d=6 i=6 c=1 r=0   sau d=6 i=3 c=2 r=0   saud=6  i=2 c=3 r=0

b) d=7  i=6 c=1 r=1 sau  d=7 i=3 c=2 r=1 sau  d=7 i=2 c=3 r=1

c) d=8 i=6 c=1 r=2.......

......................................

f) d=11 i=6 c=1 r=5 .....




16 4 16
2014-10-18T16:15:35+03:00
X:y=z,r  unde  r+6=x  , r =1,2,3,4,5
 7:6=1 rest 1
 8:6=1 rest 2
 9:6=1 rest 3
10:6=1 rest 4
11:6=1 rest 5
24 3 24